Android-Based Blended Learning Media for Computer Maintenance Lectures - Sefriani, Rini; Sepriana, Rina; Radyuli, Popi; Hakiki, Muhammad (Universitas Pendidikan Ganesha, 2022)
Advances in science and technology that move so fast provide very significant changes to human life, especially in the field of education and learning. This study aims to design and develop a combination of Android-based learning media that can be used on communication devices such as smartphones in the hope of increasing students' understanding of computer maintenance. The type of research used is research and development (R&D) using a 4D model, namely define, design, development and dissemination which produces android-based learning media products. The instrument used in this study was in the form of a questionnaire distributed to lecturers and students as well as experts to test the feasibility. based on the analysis, it was found that the feasibility test for this android-based learning media was 82.83%, with a valid interpretation of the level of validity of the use. The results of the overall practicality assessment from the practicality test were obtained at 86.34%, so that the practicality level could be interpreted as very practical to use. The results of the overall assessment of the effectiveness test for the effectiveness assessment are 100% so that it can be interpreted as being very effectively used. Thus, this learning media is valid to use, very practical to use and very effectively used in computer maintenance lectures.